Semantic Change on Imitative Slang Used by Indonesian Netizen - Savitri, Putu Weddha; Dewi, Anak Agung Sagung Shanti Sari (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and Culture, 2023)
In this digital era, the development of a language can be observed from its use on social media or audio-visual digital platforms such as Youtube, Spotify, or Tik-Tok. This can happen because social media or any digital platform has become a media to deliver any expression freely. Young generation as the largest users of it, used often non-standard language in expressing their thought and it can be led to language change. One of these changes is a change in meaning. This paper aimed to analyses the meaning changes of the words especially those that classified as imitative slang and their function. The data was taken from any written language used by netizens on the TikTok platform and YouTube. This study uses qualitative methods in data analysis. The result showed that there are a widening or expansion of meaning, metaphor, hyperbole, and degeneration or pejoration of meaning through these slang words.